Factors influencing envelope airtightness of lightweight timber-frame houses built in the Czech Republic in the period of 2006–2019. (May 2021) - Böhm, Martin; Beránková, Jitka; Brich, Jiří; Polášek, Marek; Srba, Jaromír; Němcová, Dana; Černý, Robert
Abstract: In this research, 558 family timber-frame houses newly built in the period of 2006–2019 in the Czech Republic were assessed in terms of their airtightness. The air leakage through the building envelope was evaluated via the 'blower-door' method, and the most important parameters affecting the airtightness of these types of buildings were simultaneously evaluated. In low-energy houses with natural ventilation, the mean air change rate at a pressure difference of 50 Pa (ACH50) was ascertained as 1.03 h −1, and in low-energy houses with mechanical ventilation and heat recovery, the average ACH50 value was 1.07 h −1 . Passive houses had an average ACH50 value of 0.44 h −1 . The positive effects of mandatory regulations and government subsidies were demonstrated. The ACH50 values improved with each new year of construction; this trend was especially evident for low-energy houses. A very significant influence was also found from the company conducting the construction and the construction technology being employed; an on-site construction method achieved lower ACH50 values than a method based on panel construction with a higher degree of prefabrication. The ACH50 values were also affected by the presence of a chimney and/or type of the interior airtight vapour barrier. In particular, a brick chimney body impaired the ACH50 values. Timber-frame houses with a vapour-permeable air barrier systems generally had smaller air leakage rate values than houses with a polyethylene vapour barrier. However, neither the internal building volume nor the envelope area were found to be significant parameters in terms of airtightness for the lightweight timber-frame residential houses. Highlights: The airtightness of lightweight timber-frame houses was assessed. The air change rate at 50 Pa was significantly lower than that in the past. The value of the air change rate ascertained at 50 Pa was 0.92 h −1 for 558 houses. A very significant influence was found in terms of the company conducting the construction. An on-site construction method can be used to build houses with very low ACH50 values.